Victim F : from crime victims to suspects to survivors - Huskins, Denise; Quinn, Aaron; Egan, Nicole Weisensee (Berkley, 2021)
"The shocking true story of a bizarre kidnapping and the victims' revictimization by the justice system. In March 2015, Denise Huskins and her boyfriend, Aaron Quinn, awoke from sound sleep to a nightmare. Armed men bound and drugged them, then abducted Denise and warned Aaron not to call the police or she would be killed. Aaron agonized about what to do. Finally he put his trust in law enforcement and dialed 911. But instead of searching for Denise, the police accused Aaron of her murder. His story, they told him, was just unbelievable. When Denise was let go, the police turned on her, dubbing her the "real-life Gone Girl," saying she had faked her own kidnapping. In Victim F, Aaron and Denise recount the horrific ordeal that almost cost them everything. Like too many victims of sexual violence, they were dismissed, disbelieved, and dragged through the mud. With no one to rely on except each other, they took on the victim blaming, harassment, misogyny, and abuse of power running rife in the criminal justice system. Their story is, in the end, a love story, but one that sheds necessary light on sexual assault and the abuse by law enforcement that all too frequently compounds crime victims' suffering"--